Population structure of short‐finned pilot whales in the oceanic archipelago of Madeira based on photo‐identification and genetic analyses: implications for conservation. Issue 5 (4th March 2013) - Alves, Filipe; Quérouil, Sophie; Dinis, Ana; Nicolau, Cátia; Ribeiro, Cláudia; Freitas, Luís; Kaufmann, Manfred; Fortuna, Caterina
ABSTRACT Pilot whales Globicephala spp. are known to display a hierarchical social pattern, but longitudinal data to infer population structure of short‐finned pilot whales Globicephala macrorhynchus are rare. Using data collected between 2003‐2011 in the oceanic archipelago of Madeira, the grouping structure of short‐finned pilot whales was studied using photo‐identification methods and mtDNA sequences and microsatellite markers to test the hypotheses that (1) there is at least one pelagic and one or more island‐associated communities, and (2) groups are made of related individuals, with a matrilineal social structure. Pilot whales demonstrated a large degree of variability in site fidelity, including residents (up to 14‐year interval), regular visitors and transients. The social and temporal analyses revealed a well‐differentiated society with long‐lasting relationships (of years). The genetic analyses suggested that individuals of the three residency patterns may not be genetically isolated, and that small groups are made up of related individuals, suggesting some degree of social philopatry, while large groups are probably temporary associations of smaller groups. It is proposed that the pilot whales encountered in Madeira belong to a single population encompassing several clans, possibly three clans of island‐associated whales and others of transients, each containing two to three matrilineal pods, each with a mean of 15 individuals (SD=9, range: 4‐29). We suggest that the clans interact for mating purposes when they meet. For management decisions, it is considered that the island‐associated whales should not be regarded as demographically independent populations, but instead as stable social entities to be included in governmental management plans and requiring periodic evaluation of their status. The high proportion of marked individuals and low rate of mark change encourages further research in this species. Copyright © 2013 John Wiley & Sons, Ltd.